Fabrication of a highly-efficient phosphorus-silicon-containing transparent coating to improve fire safety of poly(methyl methacrylate). (August 2022) - Zhang, Kang; Wang, Yan; Xiao, Yuling; Zheng, Yapeng; Lu, Jingyi; Ma, Chao; Hu, Yuan
Abstract: A novel phosphorus/nitrogen-containing hyperbranched polyphenylphosphate (PHP) was synthesized and it was used with 3-isocyanatopropyltrimethoxysilane (ICPTMOS) to prepare transparent and flame retardant coating for poly(methyl methacrylate) (PMMA). The content of PHP and ICPTMOS was changed to investigate the influence of silicon content on the performance of PMMA coating complexes. All coated PMMA samples are highly transparent and the pencil hardness of coatings increases with the increment of silicon content. The cone calorimeter test results indicate that the relatively low silicon content in PMMA coatings is conducive to the simultaneous reduction of heat release and smoke production. Moreover, the coatings can effectively protect the PMMA matrix in fire and with only 3.2% PHP replaced by ICPTMOS (0.08 g) in coating formulation, the fire resistance time of corresponding coated PMMA sample is extended to 1500 s. This work provides a highly-efficient strategy to concurrently improve fire safety, transparency and hardness of coating.